UJI FITOKIMIA SENYAWA AKTIF TUMBUHAN MANGGARSIH (Parameria laevigata (Juss) Moldenke) DARI HUTAN ALAM DESA MALINAU LOKSADO DAN HASIL BUDIDAYA EKSITU BANJARBARU - Sika Handayani Barus; Siti Hamidah; Trisnu Satriadi (Universitas Lambung Mangkurat, 2020)
The purpose of this study was to analyze the phytochemical contents of manggarsih (Parameria laevigata (Juss) Moldenke) from nature and cultivated exitu. The method used by Harbone method, to assay phytochemistry. The results showed that was not difference of phytochemical content of manggarsih plants originating from nature and manggarsih plant cultivated exitu in Banjarbaru. Manggarsih leaves both natural and cultivated exitu in Banjarbaru both contain saponins, quinons, tannins and steroids. Manggarsih rods from both natural and cultured produce contain flavonoids, quinons, saponins, steroidal tannins and alkaloids, while the roots contain flavonoids, quinones, saponins, tannins, triterpenoids and alkaloids. Based on these results, it suggested that people cultivate manggarsih outside the forest so as not to depend on the forest to reduce the occurrence of scarcity. Nevertheless, it is necessary to do further test of phytochemical test in quantitative way to know with certainty the content of each phytochemical compound derived from nature and cultivated exituKeywords: phytochemical, manggarsih, scarcity, cultivated exitu